2008
DOI: 10.1089/ten.tea.2007.0399
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nanofiber-Coated Surfaces on the Proliferation and Differentiation of Osteoprogenitors In Vitro

Abstract: The osteoconductive property of titanium (Ti) surfaces is important in orthopedic and dental implant devices. Surface modifications of Ti have been proposed to further improve osseointegration. In this study, three different materials, silicon (Si), silicon oxide (SiO(2)), and titanium oxide (TiO(2)), were used to construct nanofibers for surface coating of Ti alloy Ti-6Al-4 V (Ti alloy). MC3T3-E1 osteoprogenitor cells were seeded on nanofiber-coated discs and cultured for 42 days. DNA, alkaline phosphatase, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…These thin films may be useful as resilient coatings on biomedical implants, where specific biofunctionality can be imparted to the implant surface through engineering of the modular engineered ELP. 41 …”
Section: Resultsmentioning
confidence: 99%
“…These thin films may be useful as resilient coatings on biomedical implants, where specific biofunctionality can be imparted to the implant surface through engineering of the modular engineered ELP. 41 …”
Section: Resultsmentioning
confidence: 99%
“…TiO 2 surfaces containing nanofibers [36] or nanotubes [37] facilitated a higher cellular differentiation capacity than surfaces devoid of nanostructures. Zhao et al [38] found that the microroughening of Ti6Al4V surfaces by grit-blasting with hydroxyapatite/beta tricalcium phosphate particles markedly increased the expression of osteocalcin but decreased alkaline phosphatase activity.…”
Section: Discussionmentioning
confidence: 99%
“…Nanofiber sheet has been widely applied to wound site and effectively delivered drugs and recovered wound site . The application was extended to coating materials of implanting devices such as orthopedic and dental implantation and bare metal stent . Flexible sheet that is compatible for coating materials and uniformly coated states on stent were kept even with expanding state of stent according to the polymers.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] The application was extended to coating materials of implanting devices such as orthopedic and dental implantation and bare metal stent. [14][15][16] Flexible sheet that is compatible for coating materials and uniformly coated states on stent were kept even with expanding state of stent according to the polymers. Also local drug delivery system of nanofiber made it possible of development of new type of drug-eluting stent compared with previous studies of drug-eluting stents.…”
Section: Introductionmentioning
confidence: 99%